Spatial patterns of Facebook social network service: the case of Poland, Ukraine and Belarus - Puhach, Serhii Olexandrovych (Bulletin of Geography. Socio-economic Series, 2023)
Th e phenomenon of social network services (SNSs), investigated by numerous scientifi c disciplines, can hardly be overestimated in today's globalised world. However, there is a lack of studies focused on the spatial aspects of SNS development and operation. Th is article deals with peculiarities of the current distribution and main spatial tendencies of the SNS Facebook’s development in Central and Eastern Europe on the examples of Poland, Ukraine and Belarus. The spatial distribution of Facebook has the following patterns in the studied area: a relationship between the type of development of the country and the level of Facebook penetration (i.e., the “Facebook Divide”); an increase in number of users and penetration rate in developed areas (capital regions, major socio-economic centres); a progressive increase in the share of users from east to west; a large concentration of users in capitals and regional centres; the fi lter function of the state border